Segregation of Manganese Atoms during the Growth of Ge1-xMnx Nanocolumns on Ge (001) - Giang, Le Thi; An, Nguyen Manh (VNU Journal of Science: Mathematics - Physics; Vol 30 No 2, 2014)
Abstract: High resolution - transmission electron microscopy (HR-TEM), along with Reflection High-Energy Electron Diffraction (RHEED) and Laser pulse atom probe tomography (LP- APT) were used to investigate the growth kinetics of Ge 1-x Mn x nanocolumn on Ge(001) and the mechanism of Ge 1-x Mn x nanocolumn formation. The results evidence that during the deposition of Ge 1-x Mn x film, Mn atoms diffuse into the Ge matrix to form Mn-rich regions and the upward segregation of Mn atoms along the [001] direction is the origin of the Mn concentration enrichment inside the nanocolumns. Keywords: Diluted magnetic semiconductors, nanocolumns, Ge 3 Mn 5 clusters, Mn segregation.